Image Quality Assessment of Hybrid Statistical Iterative Reconstruction (H/SIR) in Comparison to Filtered Back Projection (FBP) - Arjah, H.; Osman, N. D.; ALMasri, H.; Anam, C.; Aziz, M. E. (Atom Indonesia, 2026)
Hybrid Statistical Iterative Reconstruction (H/SIR) is a method for Computed Tomography (CT) image reconstruction that provides optimal diagnostic images while reducing radiation doses compared to the standard protocol using Filtered Back Projection (FBP). This work aims to assess the image quality metrics; Signal to Noise Ratio (SNR) and Contrast-to-Noise Ratio (CNR) of Low-Dose Computed Tomography (LDCT) examination with different vendors H/SIR algorithms. Three CT scanners from different manufacturers (Philips, GE, and Siemens) were used in this work. A total of 218 clinical images were analysed. The SNR and CNR of LDCT+H/SIR images were compared with standard protocol combined with FBP. The quantitative assessments were achieved by IndoQCT software. Results showed that H/SIR preserved image quality while radiation dose was minimized.